Analysis of The Relationship Between Work-Family Conflict, Workload, Work Environment, and Job Satisfaction On Turnover Intention Among Healthcare Workers At X Hospital In Central Sulawesi - Sausan Maulida; Innocentius Bernarto (Dinasti Publisher, 2024)
This research was conducted based on findings regarding the high turnover at X Hospital Central Sulawesi. The primary objective of this study is to examine the influence of work-family conflict, workload, work environment, and job satisfaction on turnover intention among healthcare workers at X Hospital Central Sulawesi. This is a quantitative study utilizing a questionnaire for data collection, with a sample size of 171 respondents. The data analysis technique used is PLS-SEM with the SmartPLS statistical application. The results of the study found that work-family conflict has a significant and positive effect on turnover intention, workload has a significant and positive effect on turnover intention, work environment does not have a significant effect on turnover intention, and job satisfaction has a significant and positive effect on turnover intention.